Virtual Reality in Stroke Rehabilitation and Treatment: Focusing on the Patient’s Experience and Needs - Hadjipanayi, Christos; Banakou, Domna; Michael-Grigoriou, Despina (My University, 2025)
This chapter focuses on upper-limb stroke rehabilitation and virtual reality interventions that seek to facilitate the rehabilitation process. These virtual reality interventions include rule-based challenges in the form of purpose-designed exergames but also more playful and creative approaches, such as the creation of visual artworks by rehabilitation patients. The first aim of this chapter is to introduce some of the most notable virtual reality interventions in the field of rehabilitation, with primary focus on fully immersive virtual reality technology. The second aim is to provide a critical perspective toward the efficacy of virtual reality interventions and highlight potential caveats of immersive virtual reality technology for upper-limb stroke rehabilitation. This perspective derives from gaps in literature but also from research outcomes that are relevant to neuroplasticity, task engagement, and the improvement of the quality of life for stroke patients.